Optimization of low-sugar bitter gourd (Momordica charantia)-supplemented chocolate bar using mixture response surface methodology - Dizon, Kathleen Rea P.; Villarino, Blanca J. (2006)
ABSTRACT An optimized formulation was developed for the preparation of low-sugar bitter gourd-supplemented chocolate bar as a functional confection using mixture response surface methodology (RSM). The factors studied included unsweetened chocolate, bitter ground extract, and isomalt. Nine bitter gourd-supplemented chocolate bar formulations with two replications were evaluated for consumer acceptance (n = 54)for overall liking and acceptance of color, texture, sweetness, bitterness, chocolate and overall flavor using 9-point hedonic scales. The attribute intensities of the sample were also rated to explain the consumers' responses. The optimum formulation predicted to have the highest acceptance scores with two non-optimal formulations were selected and subjected to sensory evaluation to confirm the validity of the prediction models. Sensory evaluation indicated that overall texture, sweetness, bitterness and overall flavor were the significant (R^2 >0.60) attributes limiting the acceptability of low-sugar bitter gourd-supplemented chocolate bar. Superimposition of the acceptance and attribute intensity contour plots demonstrated that consumers prefer a smooth, soft, sweet and less bitter chocolate bar. Based on RSM, the optimum formulations for the chocolate bar attained were: 45-50% unsweetened chocolate, 13-21% bitter gourd extract, and 33-40% isomalt. Verification of the prediction models resulted in an overall error of 8.1289% signifying that the equations generated can predict the acceptance of the optimum formulations.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Chocolate